The identification of genes involved in the degradation of polyphosphate in Chlamydomonas reinhardtii : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science at Massey University, Palmerston North, New Zealand - Oliveira da Rocha, Catarina Sofia (Massey University, 2021)
Phosphate (P) is an essential nutrient which availability can limit the growth and survival of all organisms, including microalgae. Microalgae have been reported to absorb and accumulate P as polyphosphate (PolyP) intracellularly. This microalgal ability has interested engineers for years as it could prove valuable for P removal and recovery from wastewater. While a pathway for PolyP synthesis has been described in microalgae, little is known about the mechanisms involved during PolyP degradation in microalgae. In this study, a reproducible biochemical assay was designed to determine the kinetics of PolyP degradation in the model organism Chlamydomonas reinhardtii. For this purpose, C. reinhardtii wild-type 1690 was grown in minimal media low phosphorus (MM low-P) for 5 days prior to the addition of 10 mg L⁻¹ P. Biological triplicates were analysed, and we measured the changes in cellular P content and granular-PolyP. After the analysis of the bioassays, we extracted RNA from the treatment groups. Based on information reported in the literature regarding other organisms we selected vtc1, vtc4, ipy1, ipy3, ppa and nudix hydrolase as candidate genes encoding enzymes involved in PolyP degradation in C. reinhardtii. Quantitative PCR was used to measure the transcription of ipy1, ipy3, ppa and vtc1 genes and these were shown to be regulated after the addition of P, but we were unable to quantify vtc4 and nudix genes. To corroborate the transcriptomics data, we used insertional mutants knock down in IPY1, IPY3, PPA and Nudix hydrolase. The mutants were grown in ammonia acetate low phosphorus (low-P) media and we quantified the changes in cellular P content and granular-PolyP up to Day 13 (168-hours), after the addition of P. Based on our results, we selected Nudix hydrolase was the most likely candidate involved in the degradation of PolyP. For the first time, we took a step to better understand PolyP consumption in microalgae. This knowledge is critical for a better understanding of the function and regulation of PolyP in algae.
Keywords: 310802 Plant biochemistry